Behavior of electrical resistivity in sandy clay loam soil with respect to its strength parameters - Osman, S.B.S. (Asian Research Publishing Network, 2016)
Precise determination of engineering properties of soil is important for the proper design of any geotechnical structure. In general, the most common parameters used in computing strength of soil as currently being practiced are the cohesion (c), internal angle of friction, (F), and standard penetration test (SPT-N) values. These parameters are normally obtained from actual soil boring and extraction of samples which are then brought to the laboratory for the appropriate testing. However, bore hole drilling and sampling method is in general time consuming and very expensive and so this paper presents the results of an ongoing research on correlations of electrical resistivity with strength properties of soil with the long term objective of partially replacing soil boring with geophysical methods. Soil drilling, 1D field electrical resistivity (VES) and seismic survey and laboratory tests results were together analyzed to look into the behavior or correlations between electrical resistivity against various strength parameters. From the data obtained, the soil could be generally classified as sandy clay loam and results show that for this particular soil type, an increase in electrical resistivity produces higher angle of friction and lower cohesion with regression values of R2 = 0.5586 and R2 = 0.4693 respectively, while correlation between electrical resistivity and SPT-N depicts a polynomial curve having both increasing and downward with a regression value of R2 = 0.8399. Â© 2006-2016 Asian Research Publishing Network (ARPN).